What Governs Immediate or Delayed Cardioversion of Atrial Fibrillation by Direct Current Shock? - AL-Hamdi, Amar T.; Ali, Azad J.; Alzand, Becker S. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Aftershock delivery and direct current DC-cardioversion of atrial fibrillation may be immediate or delayed. Objective: To characterize the immediate or delayed reversion of atrial fibrillation. Methods: The study was conducted at Alhassani Heart Centre from October 2018 to February 2022. Patients diagnosed with persistent atrial fibrillation and who reverted to sinus rhythm after DC-Cardioversion were included in this case series study. Some patients showed immediate conversion to sinus rhythm while others showed delayed conversion after shock delivery. The duration of the atrial fibrillation, the ventricular rate range before the intervention, the preceding drug therapy, patient weight, and left atrial size were measured to illuminate the factors that affect the reversion format. Results: From a total of 86 patients with persistent atrial fibrillation treated with DC-cardioversion, 77 (89%) patients reverted into sinus rhythm and were included in the study. Fifty patients reverted immediately, and 27 patients reverted late. The mean ventricular rate was higher in the immediate group (138 ± 22) compared to 75 ± 18 in the delayed group. The post-conversion appearance of atrial premature beats was more in the delayed group. The left atrial size was slightly larger in the delayed group. The role of taking a preceding drug was not significant in both groups. Conclusion: The pattern of reversion in atrial fibrillation patients undergoing DC shock is governed by the ventricular rate before the reversion and the appearance of atrial premature complexes after DC shock.